The influence of perceived usefulness, perceived ease of use, compatibility and subjective norm on the use of e-money - Candrawati, Triesti; Widiastuti, Retno (European Public & Social Innovation Review, 2025)
Introduction: The advancement of digital technology has significantly transformed payment methods, positioning e-money as a prominent tool for enhancing transaction efficiency and promoting financial inclusion. Methodology: This study aims to examine the influence of perceived usefulness, perceived ease of use, compatibility, and subjective norms on the intention to use e-money. A quantitative approach was employed involving 106 accounting students from the State Polytechnic of Malang, selected through purposive sampling. Data were analyzed using multiple regression analysis, preceded by classical assumption tests. Results: The findings indicate that all four independent variables have a positive and statistically significant effect on the intention to use e-money. Discussions: The results underscore the relevance of the Technology Acceptance Model and diffusion of innovations theory in explaining digital financial adoption. The perception of ease, benefit, social influence, and alignment with personal values plays a crucial role in shaping behavioral intention. Conclusions: The study provides empirical support for the importance of user-oriented technological design and social influence in promoting e-money adoption. These insights contribute to efforts in advancing digital financial literacy and inclusion among young users, particularly within higher education environments.